Etnomathematics-Based Educational Game on Plane Geometry to Enhance Learning Motivation of Fifth-Grade Elementary School Students - Prasista, Komang Dina; I Made Suarjana; Ketut Susiani (Jurnal Media dan Teknologi Pendidikan, 2025)
This study was motivated by the low motivation of students to learn flat shapes. In addition, students' learning of mathematics is still passive because the teacher still uses the lecture method. This study aims to develop ethnomathematics-based educational games, determine validity, practicality, and effectiveness. The data collection method uses interviews, questionnaire instruments, and questionnaires. Data analysis techniques include qualitative descriptive and quantitative descriptive. The research used the ADDIE model. This study takes the subject of educational game media, while the objects are validity, practicality and effectiveness. The test subjects of this study were fifth grade students, while the object of the test was the increase in student learning motivation. The results showed that the validity of learning material experts amounted to 4.75 and the validity of learning media experts amounted to 4.35, including very good qualifications. The practicality of the product is considered very good, with a percentage of teacher response practicality of 98%, student response practicality of 92.6%. The results of the one-sample t-test showed a significance value (2-tailed) of 0.000 or p < 0.05 (5% significance level), so that the ethnomathematics-based educational game on flat building material was proven effective in increasing student learning motivation. The implication of this research is that ethnomathematics educational games can increase students' motivation and technology skills in learning mathematics.